2013
DOI: 10.1371/journal.pone.0059601
|View full text |Cite
|
Sign up to set email alerts
|

A “Bat” Is Easier to Learn than a “Tab”: Effects of Relative Phonotactic Frequency on Infant Word Learning

Abstract: Many studies have shown that during the first year of life infants start learning the prosodic, phonetic and phonotactic properties of their native language. In parallel, infants start associating sound sequences with semantic representations. However, the question of how these two processes interact remains largely unknown. The current study explores whether (and when) the relative phonotactic probability of a sound sequence in the native language has an impact on infants’ word learning. We exploit the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 75 publications
3
31
1
Order By: Relevance
“…The present findings are in agreement with previous studies of the recognition of legal or common phonotactic patterns versus illegal or uncommon phonotactic patterns in English, Dutch, Spanish, and Catalan by 9‐ to 10‐month‐old infants, in both adjacent (Friederici & Wessels, ; Jusczyk et al., , ; Mattys et al., ; Sebastián‐Gallés & Bosch, ) and nonadjacent sequences (Gonzalez‐Gomez & Nazzi, ; Gonzalez‐Gomez et al., ; Van Kampen et al., ), and they also support previous findings with infants learning French or Turkish, showing that during the second half of their first year of life, infants recognize nonadjacent phonological dependencies that characterize word forms in their native language.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are in agreement with previous studies of the recognition of legal or common phonotactic patterns versus illegal or uncommon phonotactic patterns in English, Dutch, Spanish, and Catalan by 9‐ to 10‐month‐old infants, in both adjacent (Friederici & Wessels, ; Jusczyk et al., , ; Mattys et al., ; Sebastián‐Gallés & Bosch, ) and nonadjacent sequences (Gonzalez‐Gomez & Nazzi, ; Gonzalez‐Gomez et al., ; Van Kampen et al., ), and they also support previous findings with infants learning French or Turkish, showing that during the second half of their first year of life, infants recognize nonadjacent phonological dependencies that characterize word forms in their native language.…”
Section: Discussionsupporting
confidence: 93%
“…At 10 months of age, French‐learning infants showed a preference for disyllabic words containing a Labial–Coronal sequence (e.g., beta ) over words containing a Coronal–Labial sequence (e.g., tuba ) and for monosyllabic Labial‐Coronal sequences (e.g., bad ) over words containing a Coronal–Labial sequence ( dab ) (Gonzalez‐Gomez & Nazzi, ; Nazzi et al., ). Furthermore, infants learning French were able to segment Labial–Coronal sequences (nonwords, e.g., pid ) from running speech at 10 months, but Coronal–Labial sequences (e.g., dip ) only at 13 months of age, suggesting that common sequences of nonadjacent segments can serve as a cue for word segmentation in 10‐month‐olds (Gonzalez‐Gomez & Nazzi, ) and also influence early word learning (Gonzalez‐Gomez, Poltrock, & Nazzi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, they found that 10-but not 6-month-old infants prefer to listen to LC words than to CL words even before they start producing LC and CL sequences . These findings establish that the LC bias cannot be only due to motor constraints but that this bias also reflects some perceptual learning of input regularities (which might indirectly reflect articulatory constraints; for further evidence, see data on Japanese adults and infants; Gonzalez-Gomez, Tsuji, Hayashi, Mazuka, & Nazzi, 2013;Tsuji, Gonzalez Gomez, Medina, Nazzi, & Mazuka, 2012).…”
mentioning
confidence: 51%
“…Where interactions were significant, the simple effects were examined. Recordings of DriveSafe images that had <50% of eye tracking data were not included in the analyses, consistent with the threshold adopted by other studies using similar eye tracking systems . Twenty‐eight out of 880 slide recordings (3.2%) were excluded due to poor tracking; of those that were analysed, the mean eye tracking data recorded was 91.3% (S.D.…”
Section: Methodsmentioning
confidence: 92%